2012
DOI: 10.1111/j.1469-8137.2012.04370.x
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate analysis of variation in genome size and endoreduplication in angiosperms reveals strong phylogenetic signal and association with phenotypic traits

Abstract: SummaryGenome size (C-value) and endopolyploidy (endoreduplication index, EI) are known to correlate with various morphological and ecological traits, in addition to phylogenetic placement. A phylogenetically controlled multivariate analysis was used to explore the relationships between DNA content and phenotype in angiosperms.Seeds from 41 angiosperm species (17 families) were grown in a common glasshouse experiment. Genome size (2C-value and 1Cx-value) and EI (in four tissues: leaf, stem, root, petal) were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 67 publications
0
38
1
1
Order By: Relevance
“…Annuals and biennials are more frequently endopolyploid than perennials are (Barow and Meister, 2003). In angiosperms a negative correlation between endopolyploidization and genome size has been observed (Nagl, 1976;de Rocher et al, 1990;Barow and Meister, 2003;Bainard et al, 2012). Jovtchev et al (2006) demonstrated a highly positive correlation between DNA content and nuclear volume and a significant positive correlation between nuclear volume and cell volume.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…Annuals and biennials are more frequently endopolyploid than perennials are (Barow and Meister, 2003). In angiosperms a negative correlation between endopolyploidization and genome size has been observed (Nagl, 1976;de Rocher et al, 1990;Barow and Meister, 2003;Bainard et al, 2012). Jovtchev et al (2006) demonstrated a highly positive correlation between DNA content and nuclear volume and a significant positive correlation between nuclear volume and cell volume.…”
Section: Introductionmentioning
confidence: 68%
“…Low endopolyploidy degree in leaf has been found in other Fabaceae species (Bainard et al, 2012;Barow and Meister, 2003). Fabaceae species show considerably lower cycle values than other polysomatic species, for example those in Cucurbitaceae, Chenopodiaceae (Barow and Meister, 2003) and Brassicaceae (Bainard et al, 2012;Barow and Meister, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations